2017
DOI: 10.1038/ncomms15281
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cardiomyocyte behavior in zebrafish trabeculation by Neuregulin 2a signaling

Abstract: Trabeculation is crucial for cardiac muscle growth in vertebrates. This process requires the Erbb2/4 ligand Neuregulin (Nrg), secreted by the endocardium, as well as blood flow/cardiac contractility. Here, we address two fundamental, yet unresolved, questions about cardiac trabeculation: why does it initially occur in the ventricle and not the atrium, and how is it modulated by blood flow/contractility. Using loss-of-function approaches, we first show that zebrafish Nrg2a is required for trabeculation, and usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(138 citation statements)
references
References 67 publications
5
111
1
Order By: Relevance
“…The aforementioned "gain-of function" outcome in GBT0419 appears to be different from what have be previously described in other GBT lines, as all have been to date demonstrably loss-of-function mutants (17,20,40,41,69). However, it is still possible that GBT0419 is a loss-of function allele at mRNA or even protein level, given that this mutant has a blunted rxraa response to 9-cis RA (Supplemental Figure 6B, 6C), and the activated RA signaling in GBT0419 could be the consequence of certain 'feed-forward' mechanism that has been previously recognized (47).…”
Section: Discussion Rxraa Is a Therapeutic Gene Target For Dic In Aducontrasting
confidence: 59%
See 1 more Smart Citation
“…The aforementioned "gain-of function" outcome in GBT0419 appears to be different from what have be previously described in other GBT lines, as all have been to date demonstrably loss-of-function mutants (17,20,40,41,69). However, it is still possible that GBT0419 is a loss-of function allele at mRNA or even protein level, given that this mutant has a blunted rxraa response to 9-cis RA (Supplemental Figure 6B, 6C), and the activated RA signaling in GBT0419 could be the consequence of certain 'feed-forward' mechanism that has been previously recognized (47).…”
Section: Discussion Rxraa Is a Therapeutic Gene Target For Dic In Aducontrasting
confidence: 59%
“…In GBT mutants, a monomeric red fluorescent protein (mRFP) gene in the RP2 vector is fused in-frame with the N-terminal part of the affected gene (20), which reports the expression pattern of the trapped gene as a chimeric protein (17,40,41). Because GBT0419 harbors the RP2 element in the 1 st intron of rxraa ( Figure 1A), we documented mRFP expression pattern in GBT0419, and crossed it with Tg(fli1a:EGFP) (42) to label endothelial cells and Tg(ttn:actn-EGFP) (17) to label cardiomyocytes, both with enhanced green fluorescent protein (EGFP), respectively.…”
Section: Endogenous Rxraa Is Expressed In Both Myocardial and Endothementioning
confidence: 99%
“…In previous study, we showed that while nrg1‐I is the primary isoform expressed in the heart, but both nrg1‐I and nrg1‐II are dispensable for development . Instead, a recent report described an essential role for nrg2a in zebrafish heart development, in particularly . nrg1‐III is primarily expressed in neuronal tissue with known roles in regulating myelination of developing nerves .…”
Section: Discussionmentioning
confidence: 95%
“…signaling In order to investigate what regulates Crb2a localization, we assessed the role of Nrg/ErbB2 signaling and blood flow. As previously reported, blood flow/contractility and Nrg/ErbB2 signaling are essential for cardiac trabeculation (Liu et al, 2010;Peshkovsky et al, 2011;Samsa et al, 2015;Lee et al, 2016;Rasouli and Stainier, 2017). First, to test whether blood flow regulates the localization of Crb2a in CMs, we stopped contractility and blood flow by injecting tnnt2a morpholinos (MOs) (Sehnert et al, 2002) into one cell stage embryos.…”
Section: Crb2a Localization In Developing Cms Is Modulated By Blood Fmentioning
confidence: 99%
“…Prior to trabeculation, cardiomyocytes (CMs) in zebrafish are organized as a single layer. Complex coordination of different signaling cues between endocardium and myocardium including Nrg/ErbB2 signaling (Gassmann et al, 1995;Lee et al, 1995;Meyer and Birchmeier, 1995;Samsa et al, 2013;Samsa et al, 2015;Rasouli and Stainier, 2017) and mechanical forces like blood flow/contractility (Staudt et al, 2014;Li et al, 2016), promote the delamination of a subset of CMs that seed the trabecular layer. Although recent studies have identified several key regulators of different steps in cardiac development including trabeculation, much remains unknown.…”
Section: Introductionmentioning
confidence: 99%